Closing the water cycle for industrial laundries: An operational performance and techno-economic evaluation of a full-scale membrane bioreactor system - Nicolaidis, Charalambos; Vyrides, Ioannis (My University, 2014)
To reduce the consumption of freshwater in the laundry industry, a new trend of closing the water cycle has resulted in the reuse/recycling of water. In this study, the performance of a full-scale submerged aerobic membrane bioreactor (9 m3) used to treat/reuse industrial laundry wastewater was examined over a period of 288 days. The turbidity and total solids (TS) were reduced by 99%, and the chemical oxygen demand (COD) effluent removal efficiencies were between 70% and 99%. The levels of COD removed by the membrane were significantly greater than the levels of biodegraded COD. This enabled the bioreactor to sustain COD levels that were below 100 mg/L, even during periods of low wastewater biodegradation due to bioreactor sludge. An economic evaluation of the membrane bioreactor (MBR) system showed a savings of 1.13 € per 1 m3 of water. The payback period for this system is approximately 6 years. The energy and maintenance costs represent only 5% of the total cost of the MBR system.
Keywords: Biodegradation; Laundry wastewater; Membrane retention; Payback; Recycling; Submerged membrane bioreactor